2019
DOI: 10.1002/acn3.50822
|View full text |Cite
|
Sign up to set email alerts
|

Encephalopathies with KCNC1 variants: genotype‐phenotype‐functional correlations

Abstract: Objective To analyze clinical phenotypes associated with KCNC1 variants other than the Progressive Myoclonus Epilepsy‐causing variant p.Arg320His, determine the electrophysiological functional impact of identified variants and explore genotype‐phenotype‐physiological correlations. Methods Ten cases with putative pathogenic variants in KCNC1 were studied. Variants had been identified via whole‐exome sequencing or gene panel testing. Clinical phenotypic data were analyzed. To determine functional impact of varia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(40 citation statements)
references
References 27 publications
4
36
0
Order By: Relevance
“…In the pivotal paper, out of 84 clinically confirmed PME cases without clear genetic etiology, 16 who had MEAK were found to have a heterozygous missense mutation, c.959G>A (p.Arg320His), in KCNC1, 13 of whom were unrelated. Many other types of mutations have been described in KCNC1, resulting in different phenotypic N. Barot, et al expression, such as infantile-onset developmental epileptic encephalopathy (DEE) and dysmorphic features without epilepsy (Cameron et al, 2019;Poirier et al, 2017). A recent study found that a small molecular activator of Kv3 channel (RE01) can reverse the neurophysiologic changes from mutation and may guide us towards developing a therapeutic agent for MEAK (Munch et al, 2018).…”
Section: Neurophysiologymentioning
confidence: 99%
“…In the pivotal paper, out of 84 clinically confirmed PME cases without clear genetic etiology, 16 who had MEAK were found to have a heterozygous missense mutation, c.959G>A (p.Arg320His), in KCNC1, 13 of whom were unrelated. Many other types of mutations have been described in KCNC1, resulting in different phenotypic N. Barot, et al expression, such as infantile-onset developmental epileptic encephalopathy (DEE) and dysmorphic features without epilepsy (Cameron et al, 2019;Poirier et al, 2017). A recent study found that a small molecular activator of Kv3 channel (RE01) can reverse the neurophysiologic changes from mutation and may guide us towards developing a therapeutic agent for MEAK (Munch et al, 2018).…”
Section: Neurophysiologymentioning
confidence: 99%
“…The P3 variant in ITPR1, a gene encoding a calcium channel that modulates intracellular calcium signaling, was shown to decrease calcium ion release in the endoplasmic reticulum (21). The P13 variant in KCNC1, encoding a highly conserved subunit of a potassium ion channel, was demonstrated to decrease the amplitude of current (22). In the case of ALDH7A1 (P8), which is associated with the recessive disease pyridoxine-dependent epilepsy, two variants were identified near the intronic junction; these were not canonical splice variants but were reported as variants of uncertain significance owing to the lack of evidence.…”
Section: Updated Guidelines New Variant-disease Associations and Phmentioning
confidence: 99%
“…KCNC1 p.R320H variant was found in patients with myoclonic epilepsy and ataxia due to potassium channel mutation (MEAK), which is a subtype of progressive myoclonic epilepsy (PME) with milder presentation and better prognosis (9,(16)(17)(18)(19). p.A421V was identified in patients with severe developmental and epileptic encephalopathy (DEE) (19)(20)(21). Subsequently, a wider spectrum of phenotypes designated as DE (developmental encephalopathy without seizures) has been reported to be associated with KCNC1.…”
Section: Introductionmentioning
confidence: 99%